Flawed from the "Get-Go": Lee Iacocca and the origins of transformational leadership. (August 2014) - Spector, Bert
Transformational leadership has undergone a critical reassessment. Rather than examining the state of the science or the conceptual confusion and contradictions inherent in the ongoing stream of transformational leadership research, this article adopts an historical perspective, looking back on the founding era of this influential concept. In particular, the article evaluates the use of Lee Iacocca, who became the personification of the transformational leadership ideal. While placing Iacocca's appeal into a particular socio-historical context, the article offers a critical weighing of that devise. This use of Iacocca as a personification and embodiment of the transformational leadership construct was, at best, a highly romanticized take on an individual. At worse, the use of Iacocca was misleading and disingenuous. The article concludes that two core flaws of transformational leadership—over-attribution and romanticizing traditional leadership behaviors—were present from the inception.